2013
DOI: 10.1016/j.jped.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Probiotics in the Prophylaxis of Necrotizing Enterocolitis in Preterm Neonates: A Systematic Review and Meta-analysis

Abstract: In premature newborns, the use of probiotics is effective as a prophylaxis for NEC and its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Some of the documented health claims of probiotics proposed by their authors include: stimulation of various components of the immune system, gut immune response and intestinal homeostasis [85]; prevention and treatment of diarrhoea [33,39,42,86]; improvement of faecal properties and microbiota, treatment of irritable bowel syndrome, inflammatory bowel disease and constipation [43,59,60,61,85,86]; prevention and treatment of Clostridium difficile -associated diarrhoea in adults and children [62,87]; alleviation of symptoms of lactose intolerance and other food allergies [86]; prevention of necrotising enterocolitis in preterm infants [88,89,90]; decrease in plasma cholesterol level [35,85,91]; improvement of Helicobacter pylori eradication regimens [92]; therapeutic effects by supporting the immune response of HIV-infected children and adults [93,94], anti-proliferative activity on tumour cells [95,96]; reduction of viral-associated pulmonary damage through controlling immune-coagulative responses and clearing respiratory viruses [37]; immune-stimulatory properties of low molecular mass molecules produced by probiotic bacteria [97]. Although probiotics have even been proposed as treatment for eczema [98], randomized controlled trials to date do not have sufficient evidence to recommend probiotics as primary prevention [99,100].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the documented health claims of probiotics proposed by their authors include: stimulation of various components of the immune system, gut immune response and intestinal homeostasis [85]; prevention and treatment of diarrhoea [33,39,42,86]; improvement of faecal properties and microbiota, treatment of irritable bowel syndrome, inflammatory bowel disease and constipation [43,59,60,61,85,86]; prevention and treatment of Clostridium difficile -associated diarrhoea in adults and children [62,87]; alleviation of symptoms of lactose intolerance and other food allergies [86]; prevention of necrotising enterocolitis in preterm infants [88,89,90]; decrease in plasma cholesterol level [35,85,91]; improvement of Helicobacter pylori eradication regimens [92]; therapeutic effects by supporting the immune response of HIV-infected children and adults [93,94], anti-proliferative activity on tumour cells [95,96]; reduction of viral-associated pulmonary damage through controlling immune-coagulative responses and clearing respiratory viruses [37]; immune-stimulatory properties of low molecular mass molecules produced by probiotic bacteria [97]. Although probiotics have even been proposed as treatment for eczema [98], randomized controlled trials to date do not have sufficient evidence to recommend probiotics as primary prevention [99,100].…”
Section: Resultsmentioning
confidence: 99%
“…In order to perform a systematic analysis of the available evidence on the efficacy of TNF- α in NS [13], the common approach of literature search was performed in PUBMED, EMBASE, and the Cochrane Library for relevant citations from March 1994 to August 2013. The search terms used were “TNF- α ,” “neonatal,” “neonate,” “sepsis,” “infant,” “newborn,” and “tumor necrosis factors- α ”.…”
Section: Methodsmentioning
confidence: 99%
“…Probiotics have been shown to favorably influence the development and stability of the microbiota, strengthen the mucosal barrier by trophic effects on the intestinal epithelium, and stimulate both specific and nonspecific components of the immune system [67 ▪ ,68–70]. Although the need continues for well controlled clinical studies, the strength of evidence for probiotics has been demonstrated in a number of areas including necrotizing enterocolitis in premature infants [71], preventing antibiotic-associated diarrhea [72], and countering infection and allergy related to respiratory health [73,74].…”
Section: Emerging Therapies With Multimodal Actionmentioning
confidence: 99%